Factors Affecting Youth Voting Preferences in the Philippine Senatorial Election: A Structural Equation Modelling (SEM) Analysis - Enrique Batara; Ace Kristoffer Labadan; Marozel Roa (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2021)
The Philippine elections had been characterized by the presence of a weak party system, a low information environment for voters, a history of dynastic rule, and the preponderance of media celebrities in elected political offices. These features amounted to the observation that candidate winnability in the country is discussed often as a “personality versus platform’’ issue, highlighting the importance of candidates’ personal background. This study examines certain variables associated with the voting preferences of young educated voters for the 2019 Senatorial Elections. Using a quantitative approach, this inquiry specifically sought to analyze the extent to which party identification, issue orientation, candidate orientation, and pre-election surveys affect voters’ preferences for candidates. Survey data were obtained from the 210 purposively-sampled youth-voters, and were analyzed using structural equation modelling. On the whole, the results of the study indicate the positive association between the respondents’ party identification on voting preferences, as well as the positive association between pre-election surveys and the respondents’ voting preferences. Both issue orientation and candidate orientation do not appear as significant independent variables The outcome of the study has departed from the prevailing Philippine electoral trend where candidate personality-centered factors have been pivotal for explaining Filipino voting preferences.